2011
DOI: 10.1149/2.102202jes
|View full text |Cite
|
Sign up to set email alerts
|

Room Temperature Ionic Liquid Electrolytes Based on Azepanium Imide Salts for Lithium Batteries

Abstract: Ionic liquids based on the imide salts of the dialkyl azepanium cation, AZ (R 1 , R 2 ) were synthesized, characterized, and evaluated as electrolytes in lithium batteries. Nine salts were synthesized with variation in the length of the two alkyl groups [R 1 , R 2 = methyl (1), ethyl (2), propyl (3) and butyl (4)]. It was found that the asymmetric ones with R 2 -R 1 ≥ 2 are liquids at ambient temperature. The three room-temperature ionic liquids (AZ13-TFSI, AZ14-TFSI, AZ24-TFSI) showed, in the neat form, ioni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…The LSV curves of the IM(2o1)1R series were shown as examples in Figure . Usually, for the same kind of ILs, when the R substituent in the cation structure varies, the cathodic stability or anodic stability will be changed, which was reported in many papers. The cathodic limiting potentials of IM(2o1)12TFSA and IM(2o1)13TFSA were about −2.4 and −2.3 V versus Ag/Ag + , and their anodic limiting potentials were about +1.9 and +2.2 V versus Ag/Ag + , so their electrochemical windows were about 4.3 and 4.5 V, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…The LSV curves of the IM(2o1)1R series were shown as examples in Figure . Usually, for the same kind of ILs, when the R substituent in the cation structure varies, the cathodic stability or anodic stability will be changed, which was reported in many papers. The cathodic limiting potentials of IM(2o1)12TFSA and IM(2o1)13TFSA were about −2.4 and −2.3 V versus Ag/Ag + , and their anodic limiting potentials were about +1.9 and +2.2 V versus Ag/Ag + , so their electrochemical windows were about 4.3 and 4.5 V, respectively.…”
Section: Resultsmentioning
confidence: 94%
“…20 These values illustrate the crucial effect of the size and shape of the cation in combination with the size and shape of the anion on the packing and crystallization behavior of the salt. 21 It was also observed that P 1113 FSI was the only ionic liquid that showed extra peaks below melting that can be attributed to the presence of other phases/crystalline structures of lower melting points or due to a solid-solid transition corresponding to a regular crystalline to plastic crystalline phase. 22 When LiPF 6 salt was added (to the molten state in case of P 111i4 TFSI), the m.p.…”
Section: Resultsmentioning
confidence: 98%
“…A series of azepanium with larger heterocyclic rings were synthesized by Salem et al, who found that asymmetric substituents on N afforded liquids of lower melting points. 364 The electrochemical cycling of corresponding RTIL based on these azepaniums was conducted with various anode (graphite and Li 4 Ti 5 O 12 ) and cathode (LiFePO 4 and LiCoO 2 ) chemistries, and it seemed that the extreme potentials of graphite (0.2 V) and LiCoO 2 (4.2 V) still presented a challenge to the stabilities of these RTIL. Further studies were needed to fully justify their practicality.…”
Section: Ionic Liquidsmentioning
confidence: 99%